2008
DOI: 10.1093/humrep/den293
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of transvaginal 'tenderness-guided' ultrasonography for the prediction of location of deep endometriosis

Abstract: This technique shows a high specificity and sensitivity in the detection of vaginal and rectovaginal endometriosis. Good specificity associated with a lower sensitivity was obtained in the diagnosis of deep endometriosis of uterosacral ligaments, rectosigmoid involvement or anterior deep endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 27 publications
4
171
0
2
Order By: Relevance
“…These results are consistent with Yantiss et al (35) and Koga et al (24), who suggested that advanced DIE involving the recto-sigmoid is characterized by thickening of the muscularis propria, fibrotic adhesions and convergence of the serosa. This explains the sonographic aspect of these nodules, which appear as homogeneous, hypoechoic irregularly shaped areas, described by Guerriero et al (7) as having the ''Indian head dress'' sign, and in MRI appear as hypo/iso-intense T2/T1 nodules with irregular contours (web sign).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Imentioning
confidence: 81%
See 1 more Smart Citation
“…These results are consistent with Yantiss et al (35) and Koga et al (24), who suggested that advanced DIE involving the recto-sigmoid is characterized by thickening of the muscularis propria, fibrotic adhesions and convergence of the serosa. This explains the sonographic aspect of these nodules, which appear as homogeneous, hypoechoic irregularly shaped areas, described by Guerriero et al (7) as having the ''Indian head dress'' sign, and in MRI appear as hypo/iso-intense T2/T1 nodules with irregular contours (web sign).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Imentioning
confidence: 81%
“…The ''tenderness-guided'' TVUS (tg-TVUS) technique has shown promising results in the detection of DIE (7). MRI enables precise mapping of the nodules of endometriosis and is accepted as a valid imaging technique for evaluation of DIE before surgery (3,(8)(9)(10).…”
mentioning
confidence: 99%
“…Many studies have validated the non-surgical diagnosis of endometriomas and deep endometriosis through TV-US [14][15][16][17]. The ultrasound pattern showed similar modification in all patients: DIE plaques and nodules appeared less fibrotic and more homogeneous, with illdefined contours.…”
Section: Commentmentioning
confidence: 90%
“…The presence of ovarian endometriomas and adnexal adhesions were also recorded. The diagnosis of DIE was made if at least one structure in the anterior or posterior compartment showed the presence of abnormal retroperitoneal hypoechoic linear or nodular thickening with irregular contours and no or few vessels detectable at power Doppler, as per previously described and validated ultrasonographic criteria (21,22).…”
Section: Ultrasound Examinationmentioning
confidence: 99%